Effects of split injection proportion and the second injection timings on the combustion and emissions of a dual fuel SI engine with split hydrogen direct injection. (23rd April 2019) - Li, Guanting; Yu, Xiumin; Shi, Weibo; Yao, Chuanzhao; Wang, Sen; Shen, Qingxu
Abstract: In this paper, a new kind of injection mode, split hydrogen direct injection, was presented for a dual fuel SI engine. Six different first injection proportions (IP1) and five different second injection timings were applied at the condition of excess air ratio of 1, first injection timing of 300°CA BTDC, low speed, low load conditions and the Minimum spark advance for Best Torque (MBT) on a dual fuel SI engine with hydrogen direct injection (HDI) plus port fuel injection (PFI). The result showed that, split hydrogen direct injection can achieve a higher brake thermal efficiency and lower emissions compared with single HDI. In comparison with single HDI, the split hydrogen direct injection can form a controlled stratified condition of hydrogen which could make the combustion more complete and faster. By adding an early spray to form a more homogeneous mixture, the split hydrogen direct injection not only can help to form a flame kernel to make the combustion stable, but also can speed up the combustion rate through the whole combustion process, which can improve the brake thermal efficiency. By split hydrogen direct injection, the torque reaches the highest when the first injection proportion is 33%, which improves by 1.13% on average than that of single HDI. With the delay of second injection timing, the torque increases first and then decreases. With the increase of first injection proportion, the best second injection timing is advanced. Furthermore, by forming a more homogeneous mixture, the split hydrogen direct injection can reduce the quenching distance to reduce the HC emission and reduce the maximum temperature to reduce the NOX . The split hydrogen direct injection can reduce the HC emission by 35.8%, the NOX emissions by 7.3% than that of single HDI. Highlights: Split hydrogen direct injection achieves various stratified conditions of hydrogen. Split hydrogen direct injection can make the combustion more complete and faster. Split hydrogen direct injection can improve the brake thermal efficiency. There is an optimal second injection timing for every first injection proportion. Split hydrogen direct injection can reduce HC emission and NOX emissions obviously.